Exploring the fire behaviour of thin intumescent coatings used on timber. (October 2019) - Lucherini, Andrea; Razzaque, Qazi Samia; Maluk, Cristian
Abstract: The study presented herein describes an exploratory investigation on the fire performance of intumescent coatings used on timber elements. Timber samples, uncoated or coated with three different thicknesses of a commercially available thin intumescent coating, were tested using high-performance radiant panels according to the H-TRIS fire test method. Test samples were heated for 60 min at a constant incident radiant heat flux of 50 kW/m 2 . Uncoated samples quickly ignited, while coated samples showed good adherence between the intumescent coating and the timber substrate and limited flaming. At the start of the heating exposure, the intumescent coating rapidly swelled up to a quasi-steady thickness. The presence of the intumescent coating at the exposed surface of timber samples seemed to delay the onset of timber charring and also to reduce the average charring rate after initiation of charring. The delay is proportional to the DFT of the intumescent coating, up to 40 min from the start of heating for a DFT of 2.1 mm (based on 300 °C isotherm). The experimental results described herein showed that thin intumescent coatings may be effectively used on timber for delaying the onset of charring and assuming a reduced timber charring rate during heating.